Implementation of Product Quality Improvement Using the Six Sigma Method (DMAIC) to Minimize Defects in the Reusable Diaper Industry - Afandi, Muhammad; Hermansyah, Muhammad (Borong Newinera Publisher, 2026)
Reusable diapers are becoming an increasingly popular eco-friendly option, but the industry faces challenges in maintaining product quality for customer satisfaction. This study analyzes and improves the quality of reusable diapers using the Six Sigma method using the DMAIC (Define, Measure, Analyze, Improve, Control) approach. In the Define stage, quality issues are identified through customer complaints and product inspections. The Measure stage involves collecting defect data and analyzing it using control charts. The Analyze stage utilizes Fishbone Diagrams and FMEA to identify the root causes of defects. In the Improve stage, production process improvements are made, including raw material control and standard work procedures. The Control stage ensures continuous improvement through the implementation of SOPs and regular monitoring. The results show a DPMO value of 28,577 with a sigma level of 3.41, meaning that out of 1,000,000 products, there are potentially 28,577 defects. The implementation of Six Sigma has proven effective in improving the quality of reusable